Key Factors Affecting the Value of Energy Sector Companies - Lona, Benedicta Leonie Chintia Btari; Sososutiksno, Christina; Usmany, Paul (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The purpose of this study is to empirically test the effect of Debt-to-Equity Ratio (DER) and Return on Asset Ratio (ROA), moderated by Good Corporate Governance (GCG), on the Company's Value. This research is conducted using a quantitative approach with four variables. The independent variables are Debt to Equity Ratio (DER), Return on Assets (ROA), and Good Corporate Governance as the moderating variable, while the dependent variable is the Company's Value (Price to Book Value). The study was conducted on the Indonesia Stock Exchange during the period 2021-2023, and the data were sourced from the official Indonesia Stock Exchange website, with a population and sample consisting of 31 companies in the Energy Sector, specifically the Oil, Gas, and Coal Sub-sectors. The results of the analysis using robust regression show that the independent variable (X1) does not affect Y, with a probability value greater than alpha, while the independent variable (X2) significantly affects Y. Furthermore, the interaction between variable (X1) and the moderating variable is not able to significantly moderate the effect of variable X1 on Y, and the interaction between variable X2 and the moderating variable is also not able to significantly moderate the effect of variable X2 on Y.